Active thermography for the interpretation and detection of rain erosion damage evolution on GFRP airfoils. (April 2023) - Jensen, Friederike; Jerg, Josefa Feline; Sorg, Michael; Fischer, Andreas
Abstract: Defects such as voids, which may occur during the manufacturing of wind turbine blades, have a significant impact on premature rain erosion, especially at the leading edge. Active thermography offers the potential for non-contact in-situ inspection of rotor blade leading edges. Thermographic investigations on curved and coated GFRP specimens have shown that sub-surface defects not only represent a susceptibility to erosion, but that the onset of erosion is dependent on the depth of the defects. Furthermore, the damage development of sub-surface towards surface defects can be visualized, which allows the damage stage to be assigned to an erosion stage. Graphical abstract: Highlights: Automatic detection and visualization of sub-surface and surface defect evolution by means of active thermography. Automatic differentiation between sub-surface and surface defects by means of active thermography and edge detection. Damage stage assignment of thermographic investigated rain eroded test specimens into common erosion stages.